Joint sequencing of human and pathogen genomes reveals the genetics of pneumococcal meningitis - John A. Lees (Nature Portfolio, 2019)
Streptococcus pneumoniae is a causative agent of meningitis and bacteremia. In a combined pathogen and host GWAS, Lees et al. find that host genetic variation is associated with both susceptibility and severity of pneumococcal meningitis, and specific bacterial genetic variation associated with susceptibility.